2018
DOI: 10.1088/1361-6587/aaae32
|View full text |Cite
|
Sign up to set email alerts
|

Faraday effect on stimulated Raman scattering in the linear region

Abstract: The paper presents the effect of Faraday rotation on stimulated Raman scattering (SRS). When light propagates along the magnetic field upon plasma, Faraday rotation occurs. The rotation angle can be expressed as qapproximately, where θ is the rotation angle and s is distance, n e is the electron density, n c is the critical density and B is magnetic field in unit of Gauss. Both the incident light and Raman light have Faraday effects.The angle between the polarization directions of incident light and Raman ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…When B x = 46.5 T, the Larmor radius of electrons moving at thermal velocity is equal to the waist width of the laser beam, so the transverse diffusion of the electrons is greatly weakened. And according to the result in [24], Faraday effect deflects the incident light by 0.21 rad/100 µm, and deflects the scattered light by 0.76 rad/100 µm. Therefore, both the Faraday effect and the hot electron propagation can be prominent.…”
Section: Weibel Instability Of Bsrs In Magnetized Plasmasmentioning
confidence: 95%
See 1 more Smart Citation
“…When B x = 46.5 T, the Larmor radius of electrons moving at thermal velocity is equal to the waist width of the laser beam, so the transverse diffusion of the electrons is greatly weakened. And according to the result in [24], Faraday effect deflects the incident light by 0.21 rad/100 µm, and deflects the scattered light by 0.76 rad/100 µm. Therefore, both the Faraday effect and the hot electron propagation can be prominent.…”
Section: Weibel Instability Of Bsrs In Magnetized Plasmasmentioning
confidence: 95%
“…The effects of the magnetic field on both SRS and Weibel instability have been widely studied. A longitudinal magnetic field in the plasma will affect the SRS from two aspects: on the one hand, both the incident light and scattering light have Faraday effect [24], and their deflected angles are different. As a result, the driving force of the EPW decreases, and the scattering level of SRS also decreases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to the effect of magnetic fields on LPIs. [10][11][12][13][14][15][16][17][18][19][20][21] Montgomery et al pointed out that an external magnetic field of 7.5 T can significantly increase the electron temperature and improve the laser coupling in hohlraum plasmas. [13] Li et al presented a new staged hot-electron acceleration mechanism involving the two-plasmon decay (TPD) instability in the transverse magnetic field and showed that the hot electrons generated by the forward EPW of TPD can be trapped and accelerated again by the backward EPW of TPD, eventually obtaining higher energy.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Liu et al studied the effects of an axial magnetic field on the propagation of a linearly polarized laser in plasmas and found that the reflectivity level of SRS was significantly decreased due to the Faraday rotation effect. [15] Pan et al investigated SRS of a left-handed circularly polarized laser in strongly axially magnetized plasmas. The results showed that the external axial magnetic field can not only decrease the linear growth rate and the saturation level of SRS, but also excite SRS instability in over quarter-critical density plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…The difference is that the former one induces spatial decoupling, rather than temporal decoupling. Sukhdeep Kaur et al [22] and Z J Liu et al [23] respectively derived the linear theory of SRS immersed in a static longitudinal magnetic field by fluid theory and gave the numerical solution. Afterwards, K Q Pan et al [24] carried out the PIC simulation about the SRS driven by circularly polarized laser in strongly magnetized plasma.…”
Section: Introductionmentioning
confidence: 99%